2003
DOI: 10.1115/1.1564076
|View full text |Cite
|
Sign up to set email alerts
|

Calibration Procedure for Energy Performance Simulation of a Commercial Building

Abstract: Calibration of an energy simulation with actual data has generally been considered too difficult to be part of the energy audit procedure. The purpose of this paper is to develop a systematic method using a “base load analysis approach” to calibrate a building energy performance model with a combination of monthly utility billing data and sub-metered data such as is commonly available in large buildings in Korea. The calibration procedure was specifically developed to be suitable for use in both the audit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 5 publications
1
41
0
5
Order By: Relevance
“…Therefore, energy models are difficult to calibrate for non-working hours without considering overtime as an important input. In current building simulations, the internal heat gains and HVAC operation schedules are usually deterministic schedules based on a typical weekday, weekend or holiday, either from measurement or design practice [22][23][24]. These schedules do not realistically represent overtime schedules due to their stochastic nature, and because of simplistic and idealistic data inputs that are unrepresentative of actual occupancy [25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, energy models are difficult to calibrate for non-working hours without considering overtime as an important input. In current building simulations, the internal heat gains and HVAC operation schedules are usually deterministic schedules based on a typical weekday, weekend or holiday, either from measurement or design practice [22][23][24]. These schedules do not realistically represent overtime schedules due to their stochastic nature, and because of simplistic and idealistic data inputs that are unrepresentative of actual occupancy [25].…”
Section: Introductionmentioning
confidence: 99%
“…The question raised is how much e ort and resources are necessary to produce a satisfactory model. The attempt of answer is provided with a calibration method [4]. This is the starting point for this paper, which presents a modelling and calibrating method with successive increasing levels of complexity and their impact on the results.…”
Section: Introductionmentioning
confidence: 99%
“…Haberl et al [18] and Kreider et al [19,20] used statistical mean bias error (MBE) and coefficient of variation of the root mean squared error (CV(RMSE)) to evaluate the accuracy of the predicted results of the simulation model. Pan et al [14] and Yoon et al [11] also applied the criteria as shown in Table 3 into the calibration procedure for energy simulation of commercial buildings. Several calibration approaches and guidelines have been developed that use statistical techniques as part of the calibration process [10,21].…”
Section: Initial Simulation Resultsmentioning
confidence: 99%
“…Based on the calibrated baseline models, various demand response strategies were simulated to determine how to discharge thermal mass efficiently and smoothly with no rebound in electricity demand. [11] developed a systematic calibration method using a "base load analysis approach" that calibrates a building energy performance model with a combination of monthly utility billing data and sub-metered data. The results of the case study indicated that the approach provided a reliable and accurate simulation of the monthly and annual building energy requirements.…”
Section: Introductionmentioning
confidence: 99%